PENINGKATAN HASIL DAN MOTIVASI BELAJAR MATERI EKSPONEN KELAS X DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE TGT (TEAMS GAMES TOURNAMENT) BERBANTUAN WORDWALL - Robi’atun Ni’mah, Wahyu; Vera Dewi Susanti; Samsudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to improve student learning outcomes and motivation in Exponent material in class The type of research carried out was class action research with 2 cycles, namely cycle I and cycle II. The object of this research is the learning outcomes and learning motivation of students using the TGT type cooperative learning model assisted by Wordwall. Qualitative data was obtained from observing the learning process and learning activities, while quantitative data was obtained from student test results. The research results showed that in cycle I, the percentage of learning completeness was 71.4%. Meanwhile in cycle II, the percentage of learning completeness reached 80%. Based on these gains, it shows that there has been an increase in student learning outcomes. In another aspect, it is shown that in cycle I it was 89.3%, in cycle II it was 98.2%. Based on the research results, it was concluded that the application of the TGT type cooperative learning model assisted by Wordwall was able to improve the learning outcomes and motivation of class X TKJ 2 students at SMK Negeri 5 Madiun City on Exponent material.